Non-uniform sampling finite-time control for networked control systems via event-driven transmission - Lijia Liu (Advances in Mechanical Engineering, 2016)
This article investigates the networked finite-time control problem for a class of continuous-time linear systems. A novel event-driven data transmission scheme is invoked to reduce the network loads. Moreover, the non-uniform sampling triggered by sampling jitter or the fault of hold circuits is taken into account. By employing an input-delay approach, the underlying system is first reformulated to linear system with time-varying delays. Based on the Lyapunov–Krasovskii functional method, the stabilizing controller is then designed in the finite-time control sense, such that the closed-loop system is finite-time bounded. Potential and advantage of the developed techniques are demonstrated by a numerical example and an application to damping boring bar system.